THE CORELATION BETWEEN THE LEVEL OF KNOWLEDGE OF THE MOTHER ABOUT THE PROVISION OF VITAMIN A WITH MOTHER'S COMPLIANCE WITH THE GIVING OF VITAMIN A TO INFANTS AGED 6 – 11 MONTHS AT POSYANDU MEKAR SARI AND BAKTI IBU WORK AREA BAAMANG II SAMPIT HEALTH CENTER - Puspita Sari Pribadi (Jurnal Ilmiah Hospitality, 2023)
Background: WHO ( World Health Organization ) shows that half of the 20 million children under five in Indonesia suffer from Vitamin A deficiency. Meanwhile, data from WHO, Indonesia is one of the countries where the fulfillment of Vitamin A is low (Kemenkes RI, 2020). Objective: To determine the corelation between the mother's level of knowledge about the provision of vitamin A and the mother's compliance in giving vitamin A to infants aged 6-11 months at the Mekar Sari Posyandu and Bakti Ibu in the Baamang II Sampit Health Center in 2022. Research Methods : This study uses quantitative analytical methods with a cross sectional research design. What was carried out at the Mekar Sari Posyandu and Bakti Ibu Working Area of ​​the Baamang II Sampit Health Center in 2022 with a sample of 32 mothers who had babies aged 6-11 months using a total sampling technique from primary data. Using Fisher's Exact Test. Results: The results of the respondent's analysis that there is a significant corelation between Mother's Knowledge Level About Giving Vitamin A with Mother's Compliance in Giving Vitamin A to Infants Age 6-11 Months. Refer to 32 samples, the majority of mothers had sufficient knowledge level as many as 15 people (47%) and 17 people obeyed (53%). Bivariate results are values ​​Value 0,011 ≤ 0,05. Conclusion: It is concluded that there is a Corelation Between Mother's Knowledge Level About Giving Vitamin A with Mother's Compliance in Giving Vitamin A to Infants Age 6-11 Months at the Mekar Sari Posyandu and the Bakti Ibu in the Baamang II Sampit Health Center in 2022